Pelatihan Penerapan Teknik Vertikultur dalam Rangka Pemanfaatan Lahan Pekarangan dengan Berbudidaya Tanaman untuk Peningkatan Taraf Hidup kepada Kelompok Wanita Tani Ciharashas Kelurahan Mulyaharja Bogor: Training on the Implementation of Verticulture Techniques for Optimizing Yard Land Utilization through Plant Cultivation to Enhance the Living Standards of the Ciharashas Women Farmers Group in Mulyaharja Village, Bogor - Afifah, Ulil Azmi Nurlaili; Wijaya, Aldi Kamal; Undang, Undang; Qadir, Abdul; Rusmiyati, Henny; Iswati, Asdar; Suwarno, Punjung Medaraji; Sulassih, Sulassih; Tirtana, Arif; Sayekti, Tri Wahono Dyah Ayu; Sahid, Zulfikar Damaralam (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Community Engagement Program (PPM) organized by the Seed Industry Technology Study Program, Vocational School of IPB University, aims to address the challenges faced by the Women Farmers Group (Kelompok Wanita Tani, KWT) Ciharashas in Mulyaharja Village through training on vertical hydroponic techniques. This program encompasses problem identification, training, and optimizing greenhouse facilities. Problem identification revealed key issues such as greenhouse facility damage and the limited knowledge of KWT members regarding modern cultivation techniques. The training focused on vertical hydroponic system installation, nutrient management, and plant maintenance, emphasizing the efficient use of limited land. The greenhouse was repaired to support sustainable production and serve as a training hub. The training outcomes showed significant improvements in the understanding and skills of KWT members, as evidenced by pre-test and post-test results. Members are now capable of optimizing their yards, producing high-quality harvests, and increasing income through better marketing strategies. Post-training monitoring indicated the sustainability of the vertical hydroponic activities, with KWT members actively continuing the project independently. This program successfully created long-term positive impacts, including community empowerment, increased productivity, and sustainable agricultural solutions relevant to urban communities.